Wagner’s law after more than century – increase or decrease of public expenditure stipulates economic growth? - Szlichciński, Krzysztof (Ekonomia i Prawo. Economics and Law, 2009)
The main aim of this paper is to refresh the theoretical concept called Wagner’s Law which says that economic growth should be stipulated by increasing public expenditure. Statistical data confirm that there has been a growing share of public expenditure in the national income of main countries for the past century, which may be treated as a sign of a diminishing role of the market mechanism in the process of economic development. It is not easy to prove beyond any doubt that growing public expenditure influences directly the acceleration of the economic growth rate, among others because nowadays the state is able to use instruments which are difficult to quantify, and instead of expenditure it may use, for instance, tax relaxation or tax exemptions. Observations of the long term trends lead to the conclusion that allocation of resources by the state systematically supersedes the market mechanism. When in highly developed countries the public expenditure share in the national income come close to the limit of 50%, they try hard not to exceed this threshold, although 40% share seems to be the level required by those countries.